Maternal and paternal tuberculosis is associated with increased asthma and respiratory symptoms in their offspring: a study from Northern Europe - Gyawali, Sanjay; López-Cervantes, Juan Pablo; Johannessen, Ane; Gislason, Thorarinn; Holm, Mathias; Janson, Christer; Jögi, Rain; Modig, Lars; Schlünssen, Vivi; Mustafa, Tehmina; Svanes, Cecilie (Frontiers in Allergy, 2023)
Background: Given the profound impact of tuberculosis (TB) on immunity and given murine studies suggesting that infections may influence immunity across generations, we hypothesize that parental TB might impact health and disease in future offspring. Objective: This study investigated the impact of maternal and paternal TB on offspring asthma and respiratory symptoms. Methods: We included data from the third follow-up of the Respiratory Health in Northern Europe study (RHINE). Information on own asthma status, asthma-like symptoms, and other respiratory symptoms, as well as information about parental TB and asthma, were collected using standardized questionnaires. The associations between parental TB and RHINE participants' asthma and respiratory symptoms were analyzed using multiple logistic regression, with adjustments for parental education, smoking habits, and asthma. Results: Of 8 323 study participants, 227 (2.7%) reported only paternal TB, 282 (3.4%) only maternal TB, and 33 (0.4%) reported that both parents had TB. We found a higher risk of asthma (aOR: 1.29, 95% CI: 1.05-1.57) in offspring with a history of parental TB as compared to offspring without parental TB. Parental TB was significantly associated with allergic asthma in offspring (aOR: 1.58, 95% CI: 1.29-2.05), while no significant association between parental TB and asthma without allergy (aOR: 1.00, 95% CI: 0.76-1.32) in offspring was observed. Conclusion: Results from this study indicate that parental TB might be a risk factor for offspring´s asthma and respiratory symptoms. We raise the hypothesis that the immunological impact of infections might be transmitted to influence offspring phenotype in humans.